Europejskie koleje dużych prędkości : od systemów rozproszonych do jednolitej sieci - Igliński, Hubert (European High-Speed Trains : from Dispersion Systems Towards Unified Net, 2005)
The first stage of new line connecting Paris to Lyon was opened in September 1981. This achievement is considered to be the outset of 'high-speed trains' history in Europe. Nowadays 6 countries: France, Germany, Spain, Italy, Belgium and United Kingdom altogether operate on lines almost 4000 km long, with maximum speed up to 250 km/h and more. This article presents the shift from single lines and first dispersion systems towards a unified European net.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 232-240